Level of Gadget Addiction in Children and Quality of Sleep - Riska Ratnawati; Yeni Utami (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Sleep pattern disturbances are conditions in which individuals experience changes in the quantity and quality of sleep that result in discomfort. One of the factors influencing children’s sleep patterns is habitual behaviour, particularly lifestyles characterized by excessive dependence on technology. This study aimed to analyse the relationship between the level of gadget addiction and sleep patterns among fourth- to sixth-grade elementary school students at SDN X, Madiun Regency. Methods: This study employed a cross-sectional design with a simple random sampling technique. A total of 38 students from grades 4 to 6 participated in the study. Data were analysed using the Spearman Rank correlation test to determine the association between gadget addiction levels and sleep patterns. Results: The results showed that most respondents (76.3%) had a moderate level of gadget addiction, while 15.8% had a low level of gadget use. In terms of sleep patterns, 81.6% of the students experienced sleep disturbances, whereas 18.4% did not. Bivariate analysis revealed a significant relationship between gadget addiction levels and sleep patterns (p-value = 0.002; α = 0.05). Conclusions: In conclusion, there is a significant association between gadget addiction and sleep disturbances among elementary school students. It is recommended that students regulate gadget use to improve sleep quality, and that teachers provide regular education regarding responsible gadget use to support healthy sleep patterns.